Analysis of graft survival in a trial of stem cell transplant in ALS. (22nd October 2014) - Tadesse, Tezeta; Gearing, Marla; Senitzer, David; Saxe, Debra; Brat, Daniel J.; Bray, Robert; Gebel, Howard; Hill, Charles; Boulis, Nicholas; Riley, Jonathan; Feldman, Eva; Johe, Karl; et al.
Abstract Objective The first US Food and Drug Administration–approved clinical trial to treat amyotrophic lateral sclerosis (ALS) with neural stem cell–based therapy is in progress. The goal of the current study was to identify and assess the survival of human spinal cord–derived neural stem cells (HSSCs) transplanted into the spinal cord in patients with ALS. Methods Spinal cords transplanted with HSSCs were examined from six autopsy cases. Homogenized tissues were interrogated for the presence of donor versus recipient DNA using real‐time PCR methods (qPCR). Fluorescence in situ hybridization (FISH) was performed using DNA probes for XY chromosomes to identify male donor HSSCs in one female case, and immunohistochemistry (IHC) was used to characterize the identified donor cells. Results Genomic DNA from donor HSSCs was identified in all cases, comprising 0.67–5.4% of total tissue DNA in patients surviving 196 to 921 days after transplantation. In the one female patient a "nest" of cells identified on H&E staining were XY‐positive by FISH, confirming donor origin. A subset of XY‐positive cells labeled for the neuronal marker NeuN and stem cell marker SOX2. Interpretation This is the first study to identify human neural stem cells transplanted into a human spinal cord. Transplanted HSSCs survived up to 2.5 years posttransplant. Some cells differentiated into neurons, while others maintained their stem cell phenotype. This work is a proof of concept of the survival and differentiation of human stems cell transplanted into the spinal cord of ALS patients.